Effect of COVID-19 Pandemic Restructuring on Surgical Volume and Outcomes of Non-COVID Patients Undergoing Surgery. Issue 3 (March 2022) - Shao, Connie C.; McLeod, M Chandler; Gleason, Lauren; Marques, Isabel C. Dos Santos; Chu, Daniel I.; Gunnells, Drew
Objectives: COVID-19 has caused significant surgical delays as institutions minimize patient exposure to hospital settings and utilization of health care resources. We aimed to assess changes in surgical case mix and outcomes due to restructuring during the pandemic. Methods: Patients undergoing surgery at a single tertiary care institution in the Deep South were identified using institutional ACS-NSQIP data. Primary outcome was case mix. Secondary outcomes were post-operative complications. Chi-square, ANOVA, logistic regression, and linear regression were used to compare the control (pre-COVID, Mar 2018-Mar 2020) and case (during COVID, Mar 2020-Mar 2021) groups. Results: Overall, there were 6912 patients (control: 4, 800 and case: 2112). Patients were 70% white, 29% black, 60% female, and 39% privately insured. Mean BMI was 30.2 (SD = 7.7) with mean age of 58.3 years (SD = 14.8). Most surgeries were with general surgery (48%), inpatient (68%), and elective (83%). On multivariable logistic regression, patients undergoing surgery during the pandemic were more likely to be male (OR: 1.14) and in SIRS (OR: 2.07) or sepsis (OR: 2.28) at the time of surgery. Patients were less likely to have dyspnea with moderate exertion (OR: .75) and were less dependent on others (partially dependent OR: .49 and totally dependent OR: .15). Surgeries were more likely to be outpatient (OR: 1.15) and with neurosurgery (OR: 1.19). On bivariate analysis, there were no differences in post-operative outcomes. Conclusion: Surgeries during the COVID-19 pandemic were more often outpatient without differences in post-operative outcomes. Additional analysis is needed to determine the impact of duration of operative delay on surgical outcomes with restructuring focusing more on outpatient surgeries.